Double (dual) sequential defibrillation for refractory ventricular fibrillation cardiac arrest: A systematic review. (October 2020) - Deakin, Charles D.; Morley, Peter; Soar, Jasmeet; Drennan, Ian R.
Abstract: Introduction: Cardiac arrests associated with shockable rhythms such as ventricular fibrillation or pulseless VT (VF/pVT) are associated with improved outcomes from cardiac arrest. The more defibrillation attempts required to terminate VF/pVT, the lower the survival. Double sequential defibrillation (DSD) has been used for refractory VF/pVT cardiac arrest despite limited evidence examining this practice. We performed a systematic review to summarize the evidence related to the use of DSD during cardiac arrest. Methods: This review was performed according to PRISMA and registered on PROSPERO (ID: CRD42020152575). We searched Embase, Pubmed, and the Cochrane library from inception to 28 February 2020. We included adult patients with VF/pVT in any setting. We excluded case studies, case series with less than five patients, conference abstracts, simulation studies, and protocols for clinical trials. We predefined our outcomes of interest as neurological outcome, survival to hospital discharge, survival to hospital admission, return of spontaneous circulation (ROSC), and termination of VF/pVT. Risk of bias was examined using ROBINS-I or ROB-2 and certainty of studies were reported according to GRADE methodology. Results: Overall, 314 studies were identified during the initial search. One hundred and thirty studies were screened during title and abstract stage and 10 studies underwent full manuscript screening, nine included in the final analysis. Included studies were cohort studies ( n  = 4), case series ( n  = 3), case-control study ( n  = 1) and a prospective pilot clinical trial ( n −1). All studies were considered to have serious or critical risk of bias and no meta-analysis was performed. Overall, we did not find any differences in terms of neurological outcome, survival to hospital discharge, survival to hospital admission, ROSC, or termination of VF/pVT between DSD and a standard defibrillation strategy. Conclusion: The use of double sequential defibrillation was not associated with improved outcomes from out-of-hospital cardiac arrest, however the current literature has a number of limitations to interpretation. Further high-quality evidence is needed to answer this important question.